Author Correction: Mutations in the SWI/SNF complex induce a targetable dependence on oxidative phosphorylation in lung cancer. (October 2018) - Deribe, Yonathan; Sun, Yuting; Terranova, Christopher; Khan, Fatima; Martinez-Ledesma, Juan; Gay, Jason; Gao, Guang; Mullinax, Robert; Khor, Tin; Feng, Ningping; Lin, Yu-Hsi; Wu, Chia-Chin; et al.
In the version of this article originally published, information regarding several funding sources was omitted from the Acknowledgements section. The following sentences should have been included: "This work was supported by the generous philanthropic contributions to The University of Texas MD Anderson Lung Cancer Moon Shots Program, the UT Lung SPORE 5 P50 CA07090, and the MD Anderson Cancer Center Support Grant P30CA01667. V.P is supported by R01CA155196-01A1 from the National Cancer Institute." Also, reference 18 was incorrect. The original reference was: Kim, E. S. et al. The BATTLE trial: personalizing therapy for lung cancer.Cancer Discov . 1, 44–53 (2011). It should have been: Papadimitrakopoulou, V. et al. The BATTLE-2 study: a biomarker-integrated targeted therapy study in previously treated patients with advanced non–small-cell lung cancer.J Clin. Oncol . 34, 3638–3647 (2016). The errors have been corrected in the HTML and PDF versions of this article.